Creating Extraordinary From Ordinary: High Resource Efficiency of Underdog Entrepreneurs and Its Mechanism - Zhu, Hong-Ming; Xiao, Xiong-Hui; Tang, Yanzhao (Frontiers in Psychology, 2022)
Existing theory has not documented the potential benefits of facing the challenges of underdog entrepreneurs, who may succeed unexpectedly. This research explains why, and under what circumstances, the underdog status of entrepreneurs can promote entrepreneurial success rather than just hinder it. We predict that the underdog effect has the potential to boost entrepreneurial resource efficiency when entrepreneurs hold an incremental (vs. entity) theory, enter a low-barrier (vs. high-barrier) industry, and are in a favorable (vs. unfavorable) business environment. Study 1 provides support for the positive relationship between underdog status and resource efficiency through an OLS regression analysis, which is accompanied by a moderating effect of the implicit theory, industry context, and business environment. The data was obtained from two nationwide surveys. By extending a qualitative comparative analysis (QCA) of multiple case studies, Study 2 reveals support for a synergistic effect of the above factors. Our research results examine the assumption that perceiving underdog status is detrimental and offer meaningful insights into why and when underdog entrepreneurs have good performance in entrepreneurial resource efficiency. We provide a psychological and behavioral explanation for the underdog effect, extending the underdog effect theory to the field of entrepreneurship for the first time from the perspective of the actors. Finally, theoretical contributions and practical implications are discussed by indicating the limitations of the research.